The Ariadne auf Naxos of Hugo von Hofmannsthal and Richard Strauss (1975)
The impetus for this book came from an interdisciplinary seminar taught by the authors at the University of California, Riverside, in 1967. The purpose of that seminar was to introduce students from the fields of German literature and music to the complexities and artistic merits of the opera collaborations of Richard Strauss and Hμgo von Hof- mannsthal. Although the seminar permitted us to examine in some detail all six operas that were produced, it soon became evident that a book covering all six operas would be beyond the scope of .any single publication. Since one of the striking conclusions of the seminar was the importance, indeed, the uniqueness of Ariadne auf Naxos in the history of the collaboration, it was this opera that became the focal point of in- terest. Much of the information relating to Ariadne is equally ap- plicable to their other joint works, and an understanding of Ariadne will contribute to greater appreciation of all of the Strauss-Hofmannsthal operas. Originally, we hoped to make our book a comprehensive examination of every facet of the Ariadne collaboration, but this plan was revised when the result became an unwieldy manuscript of excessive length. It was necessary, therefore, to eliminate two chapters examining Hof- mannsthal's final adaptation of Der Burger als Edelmann as a drama and also Strauss's arrangement into a suite for orchestra of the music used in that final dramatic version. Two additional chapters that were intended to show the place of Ariadne in the framework of both artists' overall creative output were also omitted. In its final form the book attempts to present in detail the ex- traordinary development of the Ariadne idea from its conception to the final operatic version. Uppermost in our minds was the intention to represent fully the viewpoint of both the composer and librettist, so as to enable the reader to comprehend the enormous personal and artistic complications which were overcome to produce this opera. Ac- cordingly, the workshop correspondence is quoted extensively; for here the reader who might otherwise be unfamiliar with these fascinatingly informative letters has the opportunity to sense the give-and-take struggle that animated this collaboration. In one sense it has been difficult to write a study that will appeal to the musicologist, the literary specialist, and also to the general reader. In some instances one group of readers may possibly feel the material to be superfluous. However, such background information as is found in the early chapters, for example, we felt was necessary for the general reader. Also, clearly, the literary specialist may not know any more about Richard Strauss than the musicologist may know about Hugo von Hofmannsthal. The book is intended to be self-contained, and for this reason, too, reviews of the premiere performance have been quoted in detail, simply because they are not readily available, and because they contribute importantly to an understanding of the initially hostile critical reception which led to the subsequent decision to revise the work. Throughout the main part of the text we have employed English for the convenience of readers who might not know German. Since the documentation in the footnotes will be of interest primarily to the specialist, we have cited this material in the original language. However, in the four chapters discussing the literary and musical interpretations of the opera, both the original German and an English translation are included on the page to facilitate reading, for locating the passages in the score, and for making the meaning of the text immediately unam- biguous. Unless otherwise indicated, all translations are the authors'; in the case of the text from Ariadne, it should especially be noted that the English is meant to be fairly literal, not poetic.